The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/1331677x.2012.11517554
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Harmonization for SME-S in Europe: Some Remarks on IFRS for SME-S and Empirical Evidences

Abstract: The debate on accounting truth is an old problem (Brilo¤ , 1979) and it is at present more and more important in harmonization process, especially involving small-and medium-sized enterprises (SMEs). Their users' needs regarding the extents and type of accounting information as well as the costs of their providing are widely discussed as the arguments for di¤ erential reporting for SMEs, although there is still more literature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(8 reference statements)
0
5
0
3
Order By: Relevance
“…As dificuldades inerentes ao processo de harmonização contábil são potencializadas no contexto das PMEs, principalmente pela necessidade informacional dos usuários e pelo custo de preparação dos relatórios contábeis (Baldarelli, Demartini, Mosnja-Skare, & Paoloni, 2012). Considerando a tentativa do IASB em padronizar as demonstrações contábeis, reduzir os custos de preparação e manter a relevância da informação, Baldarelli et al (2012) analisaram as tentativas e as dificuldades para atingir esses objetivos e implementar as IFRS para as PMEs nos países europeus.…”
Section: Estudos Anterioresunclassified
See 2 more Smart Citations
“…As dificuldades inerentes ao processo de harmonização contábil são potencializadas no contexto das PMEs, principalmente pela necessidade informacional dos usuários e pelo custo de preparação dos relatórios contábeis (Baldarelli, Demartini, Mosnja-Skare, & Paoloni, 2012). Considerando a tentativa do IASB em padronizar as demonstrações contábeis, reduzir os custos de preparação e manter a relevância da informação, Baldarelli et al (2012) analisaram as tentativas e as dificuldades para atingir esses objetivos e implementar as IFRS para as PMEs nos países europeus.…”
Section: Estudos Anterioresunclassified
“…Considerando a tentativa do IASB em padronizar as demonstrações contábeis, reduzir os custos de preparação e manter a relevância da informação, Baldarelli et al (2012) analisaram as tentativas e as dificuldades para atingir esses objetivos e implementar as IFRS para as PMEs nos países europeus. Os autores observaram que os aspectos culturais, as diferenças institucionais, ambientais, de mercado e tributação, além do formato de gestão das PMEs podem influenciar na adoção e utilização das IFRS for SMEs.…”
Section: Estudos Anterioresunclassified
See 1 more Smart Citation
“…The current condition in which 27 different systems exist within the EU is unacceptable in the long term. This has been confirmed both by institutions (European Commission, International Accounting Standards Board) and studies and publications by various authors (Baldarelli et al 2012, Paseková et al 2010). International harmonization of accounting has been defined as "the attempt to bring together different systems.…”
Section: Harmonization Of Financial Reportingmentioning
confidence: 58%
“…This research reinforces the need to identify users of SME financial statements and then to identify the predominant information needs of those users. Baldarelli et al () questioned, somewhat provocatively, if the IASB exercise of simplification is really an exercise in creating information loss for SMEs and their stakeholders! They observed that the IFRS do not fit well with an economy based on social ownership or an investor‐orientated approach, as in a developing country such as Crotia.…”
Section: Ifrs For Smes: Key Advocates Iasb's Due Process and Implicamentioning
confidence: 99%